Conditions Conducive to the Glutathionylation of Complex I Subunit NDUFS1 Augment ROS Production following the Oxidation of Ubiquinone Linked Substrates, Glycerol-3-Phosphate and Proline - Kevin Wang; Jonathan Hirschenson; Amanda Moore; Ryan J. Mailloux (MDPI AG, 2022)
Mitochondrial complex I can produce large quantities of reactive oxygen species (ROS) by reverse electron transfer (RET) from the ubiquinone (UQ) pool. Glutathionylation of complex I does induce increased mitochondrial superoxide/hydrogen peroxide (O2●−/H2O2) production, but the source of this ROS has not been identified. Here, we interrogated the glutathionylation of complex I subunit NDUFS1 and examined if its modification can result in increased ROS production during RET from the UQ pool. We also assessed glycerol-3-phosphate dehydrogenase (GPD) and proline dehydrogenase (PRODH) glutathionylation since both flavoproteins have measurable rates for ROS production as well. Induction of glutathionylation with disulfiram induced a significant increase in O2●−/H2O2 production during glycerol-3-phosphate (G3P) and proline (Pro) oxidation. Treatment of mitochondria with inhibitors for complex I (rotenone and S1QEL), complex III (myxothiazol and S3QEL), glycerol-3-phosphate dehydrogenase (iGP), and proline dehydrogenase (TFA) confirmed that the sites for this increase were complexes I and III, respectively. Treatment of liver mitochondria with disulfiram (50-1000 nM) did not induce GPD or PRODH glutathionylation, nor did it affect their activities, even though disulfiram dose-dependently increased the total number of protein glutathione mixed disulfides (PSSG). Immunocapture of complex I showed disulfiram incubations resulted in the modification of NDUFS1 subunit in complex I. Glutathionylation could be reversed by reducing agents, restoring the deglutathionylated state of NDUFS1 and the activity of the complex. Reduction of glutathionyl moieties in complex I also significantly decreased ROS production by RET from GPD and PRODH. Overall, these findings demonstrate that the modification of NDUFS1 can result in increased ROS production during RET from the UQ pool, which has implications for understanding the relationship between mitochondrial glutathionylation reactions and induction of oxidative distress in several pathologies